2008
DOI: 10.1016/j.psyneuen.2008.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Unaltered hormonal response to stress in a mouse model of fragile X syndrome

Abstract: SummaryReports in the clinical literature and studies of fmr-1 knockout mice have led to the hypothesis that, in addition to mental retardation, fragile X syndrome is characterized by a dysregulation of hypothalamic-pituitary-adrenal axis function. We have systematically examined this hypothesis by studying the effects of stress on adrenocorticotrophic hormone and corticosterone levels in adult, male fmr1 knockout mice. Initially we determined the circadian rhythms of the plasma hormone levels in both wild typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 19 publications
(25 reference statements)
8
33
0
Order By: Relevance
“…however Qin and Smith (2008) did not find any genotype differences after the same stressor when using FVB/NJ male mice. However, clearly, there may have been other methodological differences between the studies which caused the differences in the results (see Table 1 for summary of key study methodology).…”
Section: Magnitude Of Responsementioning
confidence: 66%
See 4 more Smart Citations
“…however Qin and Smith (2008) did not find any genotype differences after the same stressor when using FVB/NJ male mice. However, clearly, there may have been other methodological differences between the studies which caused the differences in the results (see Table 1 for summary of key study methodology).…”
Section: Magnitude Of Responsementioning
confidence: 66%
“…As ; Ghilan et al, 2015). Furthermore, in a more detailed analysis, Qin and Smith (2008) assessed the baseline circadian rhythm of both genotypes and found no difference at any of the six time-points tested (Qin & Smith, 2008). However, two studies did identify genotype differences, though the nature of the difference contrasted: de Diego-Otero and colleagues (2009) found that KO mice had lower corticosterone levels at baseline than WT controls; in contrast, Qin and colleagues (2011) found a main effect whereby KO mice generally had higher corticosterone than WT controls.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations